The role of acoustics in a broadcasting (Herald of Journalism, 2020)
The main tools in the broadcast are: sound, noise, music and instal- lation. All actions performed by an audible signal, implemented in a high equipment that requires journalists skills in working with new systems. It is also used to improve the acoustics of the broadcast. Acoustics plays an important role on television and radio. Despite the consonance of acoustic physics and acoustics on radio and television means different. It affects the production of high-quality programs. Also, it should be considered used a microphone to record sounds and radio broadcasting tools.
Keywords: : acoustic, internoise, installation, sound.